Soft power and political challenges - Aqeed Khalid Hammodi (Journal of Madenat Alelem University College, 2022)
Among the most prominent developments in the concept of achieving power and authority for the great powers in this time is what is termed the use of soft power. After World War II, the concept of soft power appeared in America. The war imposed many variables on American political thought to expand the vision accompanying those changes to include international forces and inevitable cultural and political dominations that keep pace with the economic and political leaps the world witnessed. America had methods of future strategic performance to ensure a wide margin of hegemony in the new century, which had to rely on soft sources of power instead of hard ones. Joseph S. Nye is one of the most prominent theorists of this idea after touching the manifestations of American decline in a world that has changed a lot, but - according to Joseph Nye - the tools of American politics have not changed, the world has become intertwined in globalized urban areas and that the United States controls the most important sources of soft power from television programs, films, media and education to Invention and sports were acquitted, so according to this opinion, the United States should employ in the future with greater focus on the most important sources of American attraction, which is the soft power that supports hegemony by extending its use, and not the other way around, as is the case with hard power that exhausts the American economy. Joseph Nye found that military and economic power, or what they are called: hard or hard power, are no longer sufficient in hegemony or control, so he calls on the United States of America to use non-military force to promote and entice its ideas and policies. Nye believes that the use of force by other major powers may pose a threat to his goals and the economic, political and even cultural aspirations of the United States.